Nutrient dynamics of corn fed to livestock in conservation-based agroecosystems in neotropical savannas - Ramírez-Iglesias, Elizabeth; Hernández-Hernandez, Rosa Mary; Rubén Iglesias, José (Revista de Ciências Agroveterinárias, 2021)
Mineral deficiencies in soil-plant-animal relations are linked to chemical properties and reproductive problems in grazing animals. The objective of this study was to determine the dynamics of K, Ca, and Mg in the green leaf biomass of two types of introduced forages, Brachiaria dyctioneura (Bd) and Centrosema macrocarpum (Cm), compared to the natural vegetation of the neotropical savannah (NS) in an agricultural ecosystem. The three types of vegetation, associated with the corn crop, served as livestock feed during the dry season. The soil’s nutrient content (0-15 cm depth), the production and nutritional dynamics of green leaf biomass, and leaf/stem relationships in the fields during the grazing period were determined. In the corn crop-livestock agroecosystem, K decreased (%) in concentration as the grazing period progressed, presenting the following trend: Bd>Cm>NS. The dynamics of Ca and Mg in green leaf biomass increased slightly (p<0.05) by the end of the grazing period for Bd and Cm, in contrast to a significant decrease in the natural vegetation of the savannah. The concentration of K in the soil did not reveal significant differences between ground cover and NS plants, and the soils under Cm evidenced the highest percentage of Ca. A higher percentage of Mg was observed in the soil planted with Cm. For the three types of vegetation, an improvement was observed in the nutritional quality of the forage and soil and in the yield (kg/ha). These findings are valuable contributions within the context of production in savannas and to forage quality for livestock.